DESAIN BANK SAMPAH DALAM MENINGKATKAN EFEKTIVITAS PENGELOLAAN SAMPAH DI DESA PEJARING - Wibowo, Rachmad Satriyo; Khairunnisa, Arini Putri; Pahrurozi; Firdaus, M.; Sopian, Lalu Femi Ihsan; Lestari, Ayu; Adni, Nani Mazjiatul; Muliana, Lisma Rizka; Istiqamah, Nur; Mudi’ah, Nisrina (Universitas Mataram, 2024)
The availability of sufficient animal feed is a major challenge for farmers, especially during the dry season. In often inadequate environmental conditions, sustainable agricultural practices are key to overcoming this problem. One creative solution that can be used is fodder processing technology through fermentation, known as silage. Silage is an animal feed made from crops stored under fermented and acidic conditions. By using silage, farmers can extend the life of feed ingredients and overcome their limited feed supply. However, obstacles in the socialization and practice of making animal feed silage in Gereneng Village include the lack of community knowledge about the implementation of forage fermentation technology as animal feed. Therefore, further guidance is needed to increase the community's understanding and motivation to adopt the use of silage for their livestock.